The Impact of Urban Expansion on Agricultural Lands in Lattakia City - شيخ ديب, سامي (Latakia University Journal -Engineering Sciences Series, 2020)
The urban sprawl at the expense of the agricultural lands is one of the most important problems that resulted from the rapid population growth in developing countries, where the agricultural lands are subject to pressure and erosion as a result of this crawl, the urbanization process and the weak deterrent urban laws. This research deals with studying the causes of this creep on the agricultural lands and studying how to reduce it through urban planning methods. Lattakia Governorate, like other Syrian cities, suffers from low agricultural land areas as a result of several factors, the most important of which is urban expansion and state policy through the development of new residential neighborhoods in or near fertile agricultural lands, in addition to the material factor through which the owners of agricultural lands located in the outskirts of cities are lured And its exploitation for non-agricultural purposes. Therefore, this research was based on the issue of studying the increasing urban sprawl of Lattakia city on these lands and the necessity of controlling it and directing it away from the highly fertile lands.It has been found through study and analysis that the agricultural specificity of the city of Lattakia is not considered when determining the areas of expansion, and the absence of laws that protect these fertile lands, as the municipalities have the right to own and organize any area whatever its agricultural value, and this is a fundamental reason for the loss of fertile agricultural lands surrounding the city. The research emphasized the necessity to direct the city’s expansion in a scientific manner that takes into account preserving natural resources and limiting their depletion